2006
DOI: 10.1016/j.jasms.2006.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic polyamide oligomers extracted from nylon 66 membrane filter disks as a source of contamination in liquid chromatography/mass spectrometry

Abstract: Background interferences are perhaps an unavoidable part of analytical detection schemes, particularly when analyzing trace level samples or when using detectors with high levels of sensitivity. In liquid chromatography, mobile phase solvents are routinely filtered using membrane filter disks to trap particulates in hopes of minimizing contamination, providing improvements in data output and instrumental operation. In this study, we report that one such filter disk leads to a significant level of contamination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…Clearly, the unfiltered solvent is much cleaner than the filtered solvent. MS analysis on these ghost peaks was performed and it was determined that these peaks match common background peaks observed for Nylon 66 [30]. Therefore, it is suggested that solvents should not be filtered or be filtered only with non-nylon type filters.…”
Section: Hplc Solventsmentioning
confidence: 99%
“…Clearly, the unfiltered solvent is much cleaner than the filtered solvent. MS analysis on these ghost peaks was performed and it was determined that these peaks match common background peaks observed for Nylon 66 [30]. Therefore, it is suggested that solvents should not be filtered or be filtered only with non-nylon type filters.…”
Section: Hplc Solventsmentioning
confidence: 99%
“…Interfering polydimethylcyclosiloxanes in ambient air were reported by Schlosser and Volkmer-Engert in 2003 [84] and cyclic polyamide oligomers leaching from nylon 66 filters into the LC solvent stream were described byÖnnerfjord in 2004 [85] and identified by Tran and Doucette in 2006 [86].…”
Section: Adducts Solvents and Polymeric Interferencesmentioning
confidence: 99%
“…The presence of extractables in a syringe filter introduces impurities in the sample. Not only the syringe filter but also any surface that comes in contact with the sample has the potential to introduce extractable impurities (6). The effect of extractables on downstream analysis is not always visible.…”
Section: Extractables From Syringe Filtersmentioning
confidence: 99%
“…Based on absorbance measurements at 214 nm, these figures clearly show that hydrophilic PTFE membranes provided the cleanest sample for analysis because these filters did not introduce any extractable impurities into the sample. Nylon filters, on the other hand, had extractable impurities that were identified as cyclic low-molecular-weight polyamide oligomers (6). PVDF filters show intermediate behavior from the perspective of extractable impurities.…”
Section: Extractables From Syringe Filtersmentioning
confidence: 99%